Coaxial bioprinting vascular constructs: A review. (5th October 2022) - Xu, Huilun; Su, Yimeng; Liao, Ziming; Liu, Zhengjiang; Huang, Xiaobo; Zhao, Liqin; Duan, Ruxin; Hu, Yinchun; Wei, Yan; Lian, Xiaojie; Huang, Di
Graphical abstract: A brief summary of coaxial printing nozzle, common bioink types (Alginate, GelMA, Collagen, Chitosan, Silk fibrin, Hyaluronic acid and Bacterial Cellulose), printing methods. Abstract: Artificial blood vessels prepared by traditional methods have disadvantages such as uncontrollable shape, size and long preparation cycle, while 3D bioprinting technology makes it possible to prepare large-scaled artificial blood vessels. This work summarizes several techniques of 3D bioprinting artificial blood vessels and compares the advantages and disadvantages of different techniques. Based on 3D bioprinting, coaxial bioprinting of small diameter hollow tube is introduced emphatically. The commonly used bioinks are introduced in details. Feasible future development of coaxial printing small diameter vascular network are discussed, including possible printing structure and construction of in situ printing vascular network.